On the relationships between commuting mode choice and public health. (March 2017) - Tajalli, Mehrdad; Hajbabaie, Ali
Abstract: This paper studies the associations that may exist between commuting mode choice and public health. For this purpose, we used Community Health Survey data collected in New York City in 2010. Obesity, blood pressure, and diabetes are used as indicators of respondents' physical health, and Non-Specific Psychological Distress as an indicator of respondents' mental health. After rigorous statistical analyses, a binary probit model was fitted for each physical and mental health indicator to quantify the associations between different commuting modes and physical/mental health. Results show that walking, as expected, is associated with a lower probability of obesity, hypertension, diabetes, and mental disorders (all statistically significant) when compared to using private transportation. Using subway is related to a lower probability of obesity and diabetes while using the city bus was linked with a higher probability of obesity (all statistically significant) compared to using personal vehicles. Finally, in comparison with using personal vehicles, working at home is associated with a higher probability of having mental disorders (statistically significant). Highlights: This paper studies the associations between commuting mode choice (i.e., private, transit, active, and homeworking) and physical and mental health in New York City. We find walking and using subway as the healthiest modes of commuting. Walking is associated with lower probability of obesity, hypertension, diabetes, and mental health disorders. Using the subway is linked to lower probability of obesity and diabetes. Homeworkers are associated with the higher probability of having mental disorders.